ATTITUDE OF STUDENTS OF ISLAMIC STUDIES PROGRAMME TOWARDS TEACHERS WHO CODESWITCH IN CLASSROOM SETTING - Noraini Mohd Noor; Ahmad Mujahideen Haji Yusoff; Noormaizatul Akmar Muhamad Nasir; Nurul Husna Yaacob (Journal of Islamic, Social, Economics and Development, 2022)
Most often, the performance of language learners is marked by the acquisition of the targeted language. In ensuring the success of learners, teachers would use any possible way to let the knowledge across. Having learned the variety of students’ preferences and backgrounds, language educators cannot limit themselves to entirely using the target language in a classroom setting. This is because linguistically challenged students feel that they were left behind because they cannot understand the language and cannot engage themselves in classroom discussions. This article utilised quantitative analysis in investigating the use of code-switching by language educators, particularly in a classroom setting. A questionnaire was distributed to 77 students from one private institution in Kelantan in measuring four components, namely students’ attitudes to code-switching towards the teacher’s persona, subject access, classroom management and interpersonal relations. The findings from the study concluded that students’ attitude toward code-switching is relatively positive.